Endovascular management of bowel ischemia secondary to portal and mesenteric vein thrombosis - Shaileshkumar S Garge; Pooja D Vyas; Bushra B Rasool; Krantikumar Rathod; Inder A Talwar (SpringerOpen, 2015)
Portal and mesenteric venous thrombosis (PMVT) is an uncommon disease, but it is a clinically important case of acute mesenteric ischemia. Its diagnosis is often delayed because of nonspecific abdominal symptoms. The treatment of PMVT involves anticoagulation therapy, alone or in combination with surgery. The addition of thrombolytic therapy to the treatment of PVMT may enhance the clearance of thrombus and hasten the clinical improvement. We herein present a case of bowel ischemia due to PVMT that was successfully treated with catheter-directed infusion of urokinase through the superior mesenteric artery and systemic anticoagulation in a patient with ascites and high blood international normalized ratio. We believe that this case demonstrates that slow and steady treatment with transarterial thrombolysis over 13 days can achieve the desired Results compared with more aggressive transhepatic or transjugular thrombectomy or surgical thrombectomy, especially in high-risk patients with ascites and high international normalized ratio.